Chemical transformations during the preparation and rehydration of reactivated virgin cements - Neshable Noel; Tommy Mielke; Gustave Semugaza; Anne Zora Gierth; Susanne Helmich; Stefan Nawrath; Doru C. Lupascu (Cement)
This paper aims to provide a thorough comprehension of the chemical transformations occurring during the thermal preparation of reactivated virgin cements (RVCes). X-ray Diffraction (XRD) analysis of RVCes reveals the reformation of the di-calcium mineral phases in two polymorphic forms: α/L-C2S and β-C2S, within the temperature range from 600 °C to 850 °C. We exactly quantify the two polymorphs α/L-C2S and α/H-C2S and distinguish their presence in the reactivation temperature range. This phase formation is corroborated by scanning electron microscopy (SEM) coupled with energy-dispersive X-ray spectroscopy (EDX). We further investigated the chemical changes that, after re-activation, take place during the 28-day rehydration period using differential scanning calorimetry (DSC), thermogravimetry (TG), XRD, and SEM, confirming the reformation of the typical hydration mineral phases. Mercury intrusion porosimetry (MIP) and compressive strength tests verified the development of strength-enhancing mineral phases in RVCs, exhibiting a mechanical strength recovery ranging from 50 % to 75 % compared to industrially produced virgin cement (VCe).